2000
DOI: 10.1055/s-2000-9001
|View full text |Cite
|
Sign up to set email alerts
|

Bedside Endosonography and Endosonography-Guided Fine-Needle Aspiration in Critically III Patients: A Way out of the Deadlock?

Abstract: Endosonography and endosonography-guided fine-needle aspiration (EUS-FNA) are now established diagnostic techniques, which are performed electively in endoscopy suites. We report here the bedside use of EUS-FNA in three critically ill patients in an intensive-care unit, with a significant impact on the outcome. A mediastinal abscess after percutaneous dilational tracheotomy was aspirated in one patient, leading to appropriate antibiotic therapy and complete recovery. A paratracheal hematoma compressing the rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 5 publications
1
15
0
Order By: Relevance
“…The high diagnostic yield of paratracheal FNA for sarcoidosis is confirmed by Annema et al 33 and Fritscher-Ravens et al, 34 who found a similar sensitivity of FNA in diagnosing sarcoidosis with a sensitivity and specificity of EUS-FNA of 100% and 94%, respectively. This cor-…”
Section: Discussionsupporting
confidence: 61%
“…The high diagnostic yield of paratracheal FNA for sarcoidosis is confirmed by Annema et al 33 and Fritscher-Ravens et al, 34 who found a similar sensitivity of FNA in diagnosing sarcoidosis with a sensitivity and specificity of EUS-FNA of 100% and 94%, respectively. This cor-…”
Section: Discussionsupporting
confidence: 61%
“…38,284 Aspiration of hematomas and mediastinal abscesses with instillation of antibiotic therapy. 285,286 Guided stenting for outlet obstruction improving the quality of life for patients with pancreatic cancer. 281 Selective injection of botulinum toxin in the muscle layer of the lower esophageal sphincter in the treatment of achalasia.…”
Section: Miscellaneous Applications Of Eus and Eus-fna Therapeuticmentioning
confidence: 99%
“…We found that the most common clinical impact made by EUS was providing a tissue diagnosis of malignancy. However, as the other two reported series [1, 2] found, diagnostic EUS provided important clinical information as well. One of our patients underwent transrectal EUS during which sampling of a pelvic fluid collection correctly excluded a suspected abscess.…”
Section: Discussionmentioning
confidence: 71%
“…Fritscher-Ravens et al [1] reported the bedside use of EUSFNA in three patients to diagnose a mediastinal abscess following tracheotomy ( n = 1), relieve pressure from a paratracheal hematoma compressing the right main bronchus ( n = 1) and diagnose lung cancer in a patient awaiting cardiac transplantation ( n = 1). The authors concluded that bedside EUS-FNA was feasible and could offer an alternative in life-threatening situations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation